HIGHER ALGEBRAS AND MESONIC SPECTRUM IN 2-DIMENSIONAL QCD - Abdalla, E.; Abdalla, MCB (Elsevier B.V., 1994)
We construct composite operators in two-dimensional bosonized QCD, which obey a W(infinity) algebra, and discuss their relation to analogous objects recently obtained in the fermionic language. A complex algebraic structure is unravelled, supporting the idea that the model is integrable. For singlets we find a mass spectrum obeying the Regge behavior.